The Effect Of Sliding Distance At Different Temperatures On The Tribological Properties Of A Palm Kernel Activated Carbon-Epoxy Composite - Mat Tahir, Noor Ayuma; Abdollah, Mohd Fadzli bin; Hasan, Rafidah; Amiruddin, Hilmi (Elsevier, 2016)
-